STUDI EROSI DAN SEDIMENTASI PADA SUB-DAS KRUENG KEUREUTO KABUPATEN ACEH UTARA - Bayu Agustian; Masimin Masimin; Azmeri Azmeri (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
The changing of land use within a watershed area causes erosion and sedimentation. Soil erosion within the watershed is controlled by the climate, nature of the soil, topography, vegetation and human activities. The loose soil materials in the runoff flow result in sedimentation from which the capacity of a built dam is reducing. The research area of this study is sub-watershed of Krueng Keureuto. This sub-watershed provides water as well as soil sedimentation to Keuruto Dam. This research aims to determine the rate of erosion and sedimentation within the sub-watershed of Krueng Keuruto in Aceh Utara District. Revised Universal Soil Loss Equation (RUSLE) model and Modified Universal Soil Loss Equation (MUSLE) model integrated into GIS were used to get the picture of spatial erosion and sedimentation at the investigated site. This research estimated the rate of erosion at the sub-watershed of Krueng Keuruto as much as 1,127 ton/ha/year or 25.684,87 ton/year. The sedimentation shows continuously building up. Annual sedimentation yield (As) is approximately 2.868,94 ton/year.